ISSUES OF PUBLIC SPACE: DECISION-MAKERS AND ART - Voica PUŞCAŞIU (Studia Universitatis Babeș-Bolyai. Philosophia)
Issues of Public Space: Decision-Makers and Art. This research addresses the problem of the way public space has been used and thought of throughout history as well as to show just how much exclusion has been part of an apparently democratic space. It will then follow Henri Lefebvre’s well-known theory on “the right to the city” in order to analyze how this is relevant for Graffiti and Street Art practices, while pointing out the seemingly inherent hypocrisy of decision makers when it comes to commissioned public artworks.